The outcomes of patients newly admitted to nursing homes after hip fracture. - Kiel, D P (1994)
OBJECTIVES. The outcomes of elderly, hospitalized patients discharged to nursing homes after hip fracture were examined. METHODS. For 2624 hip fracture patients admitted to any of 43 proprietary nursing homes between 1984 and 1988, admission assessments were examined in relation to 1-month outcomes. RESULTS. Mean patient age was 82 +/- 7 y; 85% of the sample were female. Within 1 month after discharge, 24% had returned home, 12% had been rehospitalized, 3% had died, and 61% remained in the nursing home. Characteristics significantly associated with morality included disorientation, functional dependency, neurologic diagnoses, and use of cardiac medications, antidepressants, or narcotics. Rehospitalization was significantly associated with age, gender, living with someone, being ambulatory, and functional dependency. Returning home was associated with younger age, living with someone, being ambulatory, and having no disorientation, functional dependency, or psychiatric or neurologic diagnoses, nor any pressure sores. CONCLUSIONS. Better-functioning persons and those with social support returned home; physically and cognitively impaired persons and those taking narcotics, cardiac medications, or antidepressants were likely to die; and younger men, those with social support, those with functional dependency, and those who were free of disorientation were more likely to be rehospitalized.